2007
DOI: 10.1124/jpet.107.123745
|View full text |Cite
|
Sign up to set email alerts
|

Sensitization and Activation of Intracranial Meningeal Nociceptors by Mast Cell Mediators

Abstract: Intracranial headaches such as migraine are thought to result from activation of sensory trigeminal pain neurons that supply intracranial blood vessels and the meninges, also known as meningeal nociceptors. Although the mechanism underlying the triggering of such activation is not completely understood, our previous work indicates that the local activation of the inflammatory dural mast cells can provoke a persistent sensitization of meningeal nociceptors. Given the potential importance of mast cells to the pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
130
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 150 publications
(134 citation statements)
references
References 76 publications
4
130
0
Order By: Relevance
“…Extracellular recording of direct-current potentials indicated that PGD 2 perfusion caused a depolarization response of vagal C fibers (25). However, in another study using in vivo electrophysiological single-unit recording from rat trigeminal ganglion, PGD 2 failed to sensitize meningeal nociceptors (34). In contrast, responses of spinal afferent neurons to PGD 2 are different from responses of nodose and DRG neurons.…”
Section: Discussionmentioning
confidence: 91%
“…Extracellular recording of direct-current potentials indicated that PGD 2 perfusion caused a depolarization response of vagal C fibers (25). However, in another study using in vivo electrophysiological single-unit recording from rat trigeminal ganglion, PGD 2 failed to sensitize meningeal nociceptors (34). In contrast, responses of spinal afferent neurons to PGD 2 are different from responses of nodose and DRG neurons.…”
Section: Discussionmentioning
confidence: 91%
“…PGD 2 is the most abundant PG released from inflammatory cells at sites of inflammation (37). Although PGD 2 can inhibit postspike hyperpolarization of nociceptors in vagal afferents (38), we and others (39,40) reported that it is unable to directly excite DRG or trigeminal neurons. Thus, although its relevance in nociception remains per se questionable, the role of all PGD 2 -derived cyclopentenone metabolites (20) should be considered in pain transmission.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, these joint preparations are the only model in which prostaglandins by close-arterial injection caused spike discharge with short delay. In the anesthetized rat, PGE 2 potentiated the response of pulmonary C-fibers to lung inflation and PGI 2 , but not PGD 2 , increased responses of meningeal nociceptors to mechanical stimulation (287,796).…”
Section: Prostanoid-induced Sensitization To Mechanical Stimulimentioning
confidence: 99%